Pemetaan dan Strategi Pemerintah dalam Mengembangkan Agroindustri Olahan Ubi Jalar di Kabupaten Karanganyar - Natalia Kris Tri Astuti; Darsono Darsono; Mohd. Harisudin (University of Jember, 2018)
Karanganyar Regency is an area that has great potential for agroindustry development. Equivalance with development priorities in this district, industry and agriculture have an important role. Agroindustry processing can improve the performance of the agricultural sector. The purpose of this research is to find out the priority map of agroindustry in Kranganyar Regency, to know the position of competing sweet potato agroindusty, and to formulate priority of development strategy of sweet potato agroindustry in Karanganayar Regency. The basic method of this research is descriptive analytic. Priority agroindustry was analyzed by Delphi method, and the determination of competing position and alternatives strategy was analyzed with Internal-External Matrix (IE) and Grand Strategy Matrix. The decision on strategy selection is determined by Quantitative Startegic Planning Matrix (QSPM). The results showed that sweet potato agroindustry as leading agroindustry in Karanganyar Regency. Based on IE matrix analysis, the position of competing sweet potato agroindustry is in quadrant II (product development strategy and market penetration). Based on the Grand Strategy Matrix, the position of sweet potato agroindustry is in quadrant I which means having perfect strategic position. Based on QSPM obtained the most appropriate strategy recommendation of sweet potato agroindustry is product development strategy.